Pelatihan Pembuatan Bubuk Cabai dan Pemanfaatannya Bagi Siswa SMK Negeri 1 Bawen - Dewi Larasati; Aldila Sagitaning Putri; Maria Sudjatinah (Institut Teknologi dan Bisnis Semarang, 2025)
SMK Negeri 1 Bawen is located in Bawen District, Semarang Regency. Students of SMK Negeri 1 Bawen are prepared to become skilled middle-level workers in the agricultural processing industry. In addition, they are also equipped with entrepreneurial activities based on agricultural processing. So that graduates of SMK Negeri 1 Bawen are spread throughout the archipelago and work in various sectors of the Business and Industry World. The purpose of this community service activity is: To provide additional knowledge to students at SMK Negeri 1 Bawen about how to make chili powder, make chili cookies and marinate chicken with lavel seasoning, as provisions for them to work in various sectors of the Business and Industry World. The implementation of this activity provides explanations with leaflets and direct practice in front of the participants of the activity, namely 68 students of SMK Negeri 1 Bawen and three accompanying teachers. This community service activity can be concluded that: Students increased their knowledge and skills in making chili powder, processing chili cookies and marinating chicken with lavel spices and the responses of students participating in the activity showed interest and were able to process chili cookies and marinating chicken with lavel spices.